Comparative effectiveness of "liberal" and "restrictive" modes of intraoperative infusion-transfusion therapy in lung transplantation - A. M. Talyzin; S. V. Zhuravel; M. Sh. Khubutiya; E. A. Evgeniy A. Tarabrin; N. K. Kuznetsova (Трансплантология (Москва))
Introduction. Recently, researchers have paid considerable attention to the strategy of intraoperative infusiontransfusion therapy in traumatic surgical interventions. The choice of a “restrictive” regimen during surgery in many studies has reduced the incidence and severity of intra- and postoperative complications.Objective. Comparison of the effectiveness of "liberal" and "restrictive" intraoperative infusion-transfusion therapy in lung transplantation.Material and methods. The study included 58 patients who underwent bilateral lung transplantation at N.V. Sklifosovsky Research Institute for Emergency Medicine in the period 2012-2019. The patients were divided into 2 groups: the comparison group included 31 patients, the total volume of intraoperative infusion-transfusion in whom was 14386.9 ± 1310.0 ml (16.5 ml/kg/h). Group II consisted of 27 patients; their total volume of intraoperative infusion-transfusion during surgery was 10251.3 ± 740.1 ml (12.9 ml/kg/hour). The analysis we performed included the volume and composition of intraoperative infusion-transfusion therapy, the volume of blood loss, clinical and laboratory data, the duration of mechanical ventilation, the frequency of intraoperative use of veno-arterial extracorporeal membrane oxygenation and the duration of its use after surgery, mortality.Results. When using the "restrictive" fluid therapy for lung transplantation, we observed a decrease in the volume of intraoperative blood loss by 1.3 times, the volume of transfusion of blood components, including fresh frozen plasma by 37%, erythrocyte suspension by 3.1 times, and instrumental reinfusion of autoerythrocytes by 1.56 times. At the same time, we revealed a decrease by 2.7 times in the duration of the mechanical ventilation use, a decreased frequency of using veno-arterial extracorporeal membrane oxygenation during surgery by 1.3 times, and a decreased duration of using veno-arterial extracorporeal membrane oxygenation after surgery by 2.3 times. Mortality was 38.7% in group I, and 30.7% in group II.Conclusion. The “restrictive” approach to intraoperative infusion-transfusion therapy in lung transplantation seems a promising new trend requiring further study and gaining the experience.